New advances in the treatment of thin endometrium - Wang, Yidi; Tang, Zunhao; Teng, Xiuxiang (Frontiers in Endocrinology, 2024)
Thin endometrium (TE) is defined as a mid-luteal endometrial thickness ≤7mm. TE can affect endometrial tolerance, leading to lower embryo implantation rates and clinical pregnancy rates, and is also associated with impaired outcomes from assisted reproductive treatment. Herein, we systematically review TE causes, mechanisms, and treatments. TE pathogenesis has multiple causes, with the endometrium becoming thinner with age under hormonal influence. In addition, uterine cavity factors are important, as the inflammatory environment may affect expressions of certain genes thereby inhibiting endometrial stromal cell proliferation and promoting apoptosis. Long-term oral contraceptive use or the use of ovulation-promoting drugs are also definite factors contributing to endometrial thinning. Other patients have primary factors, for which the clinical etiology remains unknown. The main therapeutic strategies available for TE are pharmacological (including hormonal and vasoactive drugs), regenerative medicine, intrauterine infusion of growth factor-granulocyte colony-stimulating factor, autologous platelet-rich plasma, and complementary alternative therapies (including traditional Chinese herbal medicine and acupuncture). However, the associated mechanisms of action are currently unclear. Clinical scholars have proposed various approaches to improve treatment outcomes in patients with TE, and are exploring the principles of efficacy, offering potentials for novel treatments. It is hoped that this will improve TE tolerance, increase embryo implantation rates, and help more couples with infertility with effective treatments.